PENGARUH SEKTOR INDUSTRI TERHADAP PENINGKATAN TENAGA KERJA DI KABUPATEN MAGELANG - Rian Destiningsih; Safira Ayu Murti (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2020)
The high increase in labor is due to the high rate of population growth. This will certainly result in increased unemployment if not followed by increased employment. In Magelang Regency, one sector that has a big influence on employment is industrial sector activities, especially in 2014 - 2018. In this study, the aim is to describe how the industrial sector influences employment absorption in Magelang Regency in 2014 - 2018. With using industrial and labor samples of 21 sub-districts in Magelang Regency with a quantitative descriptive approach and using multiple linear regression. The variable used is labor as the dependent variable, while the independent variable is the number of medium and large industries. The results of the study explain that the industry is having a significant influence on employment in Magelang District in 2014 - 2018. Likewise, large industries which have a significant influence on employment in the Magelang Regency. It can be concluded that the two independent variables have a significant influence on employment in Magelang District in 2014 - 2018.